AB0128 A simplified method to determine joint loading as a surrogate marker of pain/disability in a canine model of osteoarthritis, validated using force plate analyses as a gold standard. (23rd January 2014) - Wiegant, K.; Hazewinkel, H.A.; Doornebal, A.; Barten-van Rijbroek, A.D.; Mastbergen, S.C.; Lafeber, F.P.
Abstract : Background: In humans, evaluation of tissue structure changes in OA is performed indirectly by use of surrogate markers, e.g. imaging and/or biochemical markers. In contrast, pain/disability can be validated directly, with questionnaires. A direct evaluation of tissue changes can be performed in detail in animal models of OA, however, evaluation of OA pain/disability is challenging. For dogs, force plate analysis (FPA) is a widely used method which provides detailed information of joint loading (3 degrees of freedom; brake (Fy max), stance (Fz) and propulsion (Fy min) force). Unfortunately, this technique is time consuming and needs prolonged training. Therefore, a simplified method of studying joint loading was developed: a mobile weighing platform with 4 individual scales. The loading of the hind stifle joints was evaluated during progression of experimentally induced OA and, primarily, compared to FPA-Fz. Objectives: Can the 4-plates balance be used as an intermittent analysis, and partially replenish FPA, in measurement of joint unloading in an canine OA model? Methods: In twelve mixed breed (mongrel) dogs experimental OA was induced in the right stifle joint according to the Groove model 1 . Twice at baseline and at every 5 weeks FPA was performed, as well as the 4-plates balance measurements. Five measurements of 10 seconds were performed and analysed. The average of these 5*10 sec measurements were compared to the FPA-Fz. In this first analyses baseline values (before surgery) and 10 weeks values (after surgery) were analysed, because the 5 week condition might still include pain/disability due to surgery. Results: By use of the 4-plates balance a decrease in loading of the OA right hind leg was found from 2.8±0.2kg at baseline to 2.5±0.2kg at 10 weeks follow-up (p<0.05). A similar pattern was seen for the FPA-Fz from 4.5±0.1N to 4.3±0.1N (p<0.01). A positive linear correlation was found between the delta as well as percentage decrease in loading of the right OA hind leg (10 weeks compared to pre-treatment) for both methods (R=+0.27 and R=+0.33, respectively; both p<0.03). The change in loading between the left control and the right OA leg at baseline was -0.6±0.3kg (ns) and increased to -1.0±0.3kg at 10 weeks follow-up (p<0.003). The same was found for FPA-Fz, from +0.1±0.1N at baseline (ns) to -0.3±0.1N at 10 weeks (p<0.01). Also for this difference between the control and OA hind joints a positive linear correlation existed between the 4-plates balance and the FPA-Fz (R=+0.46, p<0.007). Similar, statistically significant relations were found for the 4-plates balance and FPA-Fy max, but not for FPA-Fy min. Conclusions: Pain/disability due to OA is difficult to determine in animal models. The present study clearly demonstrates that the 4-plates balance is a useful method to measure pain/disability due to OA in dogs. The technique is less expensive, less time-consuming and can be performed at any location. Although, FPA is clearly a more elaborated technique and provides more information about gait and different forces and the 4-plates balance is a more static measurement, the latter may be of added value in evaluating pain/disability in canine models of OA. References: Mastbergen et al. Osteoarthritis and Cartilage 2006. Disclosure of Interest: None Declared